2011
DOI: 10.2147/ijn.s22189
|View full text |Cite
|
Sign up to set email alerts
|

Histological study of the biodynamics of iron oxide nanoparticles with different diameters

Abstract: The biodynamics of ultrasmall and small superparamagnetic iron oxide (USPIO and SPIO, respectively) particles that were injected intraperitoneally into 36 C57BL/6 mice were investigated chronologically. Their distribution was studied histologically at six time points by measuring iron-positive areas (μm2) in organ sections stained with Prussian blue. The uptake of the differently sized particles was also compared by cultured murine macrophages (J774.1). Iron-positive areas in the liver were significantly large… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 30 publications
2
23
0
Order By: Relevance
“…Other injection routes such as intra-peritoneal (IP) 255-257 , retroorbital, 51, 58 , intravitreal (inner cavity of the eyes for intraocular drug delivery), 258, 259 intra-muscular and subcutaneous injections have also been used as alternative methods for administration of the IONPs. Tsuchiya et al .…”
Section: Ionps Pharmacokineticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other injection routes such as intra-peritoneal (IP) 255-257 , retroorbital, 51, 58 , intravitreal (inner cavity of the eyes for intraocular drug delivery), 258, 259 intra-muscular and subcutaneous injections have also been used as alternative methods for administration of the IONPs. Tsuchiya et al .…”
Section: Ionps Pharmacokineticsmentioning
confidence: 99%
“…Tsuchiya et al . 255 showed that intra-peritoneally injected IONPs mainly distributed in liver, lymph nodes and lung. Kim et al 256 showed that IP injected IONPs can pass the blood-brain- and blood–testis-barriers in addition to usual accumulation in MPS organs.…”
Section: Ionps Pharmacokineticsmentioning
confidence: 99%
“…Khurana et al as the liver (31,32), the spleen (31), lymph nodes (32,33), and bone marrow (34)(35)(36). The relatively large nanoparticles, which have a size on the order of plasma proteins, initially distribute in the blood pool, where they cause strong T1 and T2 relaxation time enhancement (37).…”
Section: Molecular Imaging: Mr Imaging Monitoring Of Macrophage Migramentioning
confidence: 99%
“…Of note is the fact that the size of iron oxide nanoparticles determines the efficiency of cell up-take, with much higher labeling efficiency for small nanoparticles ca. 70 nm diameter (SPIO), than for ultra-small iron oxide nanoparticles (USPIO) [137]. One of the SPIO formulations (Feridex®) approved by the Food and Drug Administration (FDA) in 1996 as a liver contrast agent, following the development of methods that facilitated the labeling of non-phagocytes, including stem cells, was extensively used and characterized in preclinical research, with the intention to use Feridex® clinically thereafter [138140].…”
Section: Stem Cell Labels and Tracersmentioning
confidence: 99%